1984
DOI: 10.1177/000331978403500107
|View full text |Cite
|
Sign up to set email alerts
|

Popliteal Venous Aneurysm as a Source of Pulmonary Emboli in a Male: Case Report

Abstract: A 48 year old male was admitted with pulmonary emboli. Subsequent investigation revealed the most probable source to be a left sided popliteal venous aneurysm. A second venogram performed shortly after the first did indeed reveal thrombus originating in the aneurysm and propagating up the superficial femoral vein. Popliteal venous aneurysm is an extremely rare entity, which heretofore has been described only in female patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 3 publications
0
11
0
3
Order By: Relevance
“…They may occur in the absence of varicose veins. 1,2,6 Generally, trauma, inflammation, congenital weakness, or degenerative changes must be considered as possible causes.2 Rarely, venous aneurysms are caused by cardiovascular diseases, such as heart failure, producing increased pressure in the venous system. A significant diminution in the number and size of smooth muscle and elastic fibers in the walls of these aneurysms is a common finding.…”
Section: Discussionmentioning
confidence: 99%
“…They may occur in the absence of varicose veins. 1,2,6 Generally, trauma, inflammation, congenital weakness, or degenerative changes must be considered as possible causes.2 Rarely, venous aneurysms are caused by cardiovascular diseases, such as heart failure, producing increased pressure in the venous system. A significant diminution in the number and size of smooth muscle and elastic fibers in the walls of these aneurysms is a common finding.…”
Section: Discussionmentioning
confidence: 99%
“…Experience with two fatal cases in the literature showed that despite therapeutic levels of an anticoagulant, thrombus may continue to form and embolize [7,18]. Moreover six of the 10 patients who were initially treated with anticoagulation presented a recurrent thrombosis in the popliteal fossa or PE before having surgical correction of the aneurysm [5,11,12,18,19,59]. Since recurrence of PE after surgery has never been reported and given the high risk of recurrence of thromboembotic events with anticoagulation alone surgical treatment is indicated in all symptomatic patients.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Popliteal vein aneurysms are known to thrombose and may result in pulmonary embolism, [16][17][18] even during full anticoagulating therapy. 17,19 In the thorax and abdomen they may become symptomatic when they compress local organs.…”
Section: Discussionmentioning
confidence: 99%